2007
DOI: 10.3201/eid1312.070384
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Methicillin-ResistantStaphylococcus aureusof Animal Origin in Humans

Abstract: MRSA from an animal reservoir has recently entered the human population and is now responsible for >20% of all MRSA in the Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
321
3
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 399 publications
(344 citation statements)
references
References 21 publications
15
321
3
5
Order By: Relevance
“…In other recent Dutch studies resistance to trimethoprim-sulfamethoxazole was not or hardly ever found in MRSA in pigs and humans [11,12], hence this resistance might be currently emerging. The pattern of resistance of the MRSA samples in our study was otherwise comparable to that in other recent studies [11][12][13].…”
Section: Impact Of Nt-mrsa In Dutch Health-care Systemsupporting
confidence: 91%
“…In other recent Dutch studies resistance to trimethoprim-sulfamethoxazole was not or hardly ever found in MRSA in pigs and humans [11,12], hence this resistance might be currently emerging. The pattern of resistance of the MRSA samples in our study was otherwise comparable to that in other recent studies [11][12][13].…”
Section: Impact Of Nt-mrsa In Dutch Health-care Systemsupporting
confidence: 91%
“…In 2003, a new type of MRSA (ST398) emerged in Dutch hospitals and has been found particularly in persons having contact with pigs or veal calves [5][6][7]. Since these first notifications, this new type has been increasingly isolated [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the carriage of MRSA is the general population is low [1,2] , this policy consists mainly of screening people from foreign hospitals and/or contacts of known MRSA positive patients. In July 2006 these guidelines were changed when it became clear that contact with pigs and/or veal calves was a risk factor for MRSA carriage [3][4][5][6]. Consequently, persons in contact with these types of livestock were included in the risk groups.…”
Section: Introductionmentioning
confidence: 99%